Variação da temperatura de armazenamento em atmosfera controlada dinâmica de maçãs ‘maxi gala’ - Wendt, Lucas Mallmann (2021)
The increase of demand for quality apples throughout the year requires improvements in storage technology. Dynamic controlled atmosphere (DCA) storage that uses extremely low oxygen levels has been widespread worldwide, as it maintains the quality of apple stored for long term. Greater quality maintenance is possible because DCA allows determine the lowest oxygen limit (LOL) tolerated by apples. In addition to the technology to determine the LOL, temperature is one of the factors that most affects fruits quality during storage, because it affects the speed of chemical and biochemical reactions. This dissertation is composed of two papers with the following objectives: [1] To evaluate the effect of higher temperatures (3.0 ° C) and different strategies of temperature variation during DCA storage monitored by respiratory quotient 1.3 (DCA-RQ 1.3), comparing with different temperatures maintained constant in DCA-RQ 1.3 and with conventional controlled atmosphere (CA) storage with and without 1-methylcyclopropene (1-MCP) application; [2] Identify if low temperature in the first 30 days or during 240 days of storage in ACD-QR 1,3, improve the maintenance of physical and chemical quality, compared with CA and DCA storage monitored by chlorophyll fluorescence (DCA-CF), with and without 1-MCP application. ‘Maxi Gala’ apples were stored for 9 months in a controlled atmosphere (AC), AC+1-methylcyclopropene (1–MCP), dynamic controlled atmosphere monitored by chlorophyll fluorescence (ACD-FC) with and without 1-MCP application and ACD- QR 1.3 at constant temperatures of 0.5, 2.0 and 3.0 °C and temperature variation strategies (0.5/30d+3.0/240d °C), (0.5/30d+2.0/240d °C), (2.0/30d+3.0/240d °C), (0.5/30d+2.0/30d+3.0/210d °C) and (2.0/30d+0.5/240d °C) plus 7 and 14 days shelf life at 20 ºC. The storage of apples in DCA-RQ 1.3 at 2.0 °C results in fruit with higher physical-chemical quality, after 7 and 14 at 20 °C. After storage for another 14 days at 20 °C, the DCA-RQ 1.3 regardless of temperature maintained better physical-chemical quality compared to conventional CA with or without 1-MCP application. Temperature variation with (0.5/30d+2.0/240d °C) and (2.0/30d+3.0/240d °C) resulted in high flesh firmness and healthy fruit, due to lower flesh breakdown and decay incidence. In addition, the best temperature variation strategy in DCA-RQ 1.3 is the use of low temperature at the end of storage (2.0/30d+0.5/240d °C) or constant temperatures of 2.0 °C, which resulted in fruit with higher physical-chemical quality, after 7 and 14 days at 20 °C. Fruit stored in DCA-CF with or without 1-MCP application, showed physical-chemical qualities similar to those stored in DCA-RQ 1.3 regardless of temperature, after 14 days at 20 °C. Fruit stored in conventional CA with and without 1-MCP, after 7 and 14 days at 20 °C, showed lower flesh firmness and healthy fruit percentage, due to the high flesh breakdown and decay incidence. Therefore, the best storage conditions of apples for long periods, observed in this dissertation, follows the following order: DCA-RQ 1.3 at 2.0 °C better than ACD-QR 1.3 at 0.5, 3.0 °C and with temperature variation equal to DCA-CF with or without 1-MCP better than CA better than CA+1-MCP.